2019
DOI: 10.4038/kjm.v7i2.7576
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Post-Retirement Employment in Sri Lanka

Abstract: Sri Lanka has been undergoing the impact of population ageing. Many structural and behavioral changes begin to occur in the population as a result of this demographical shift. Reemployment after the formal retirement of employees increasingly becomes usual routinely marking it as a significant trend it in the economy. Therefore, there should be some significant determinants which determine this behavior of working after retirement in Sri Lanka. A quantitative and exploratory research study was launched as a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…1 shows the PRISMA flowchart illustrating the search strategy. Quality assessment for each article is demonstrated in Table I with high-quality in seven studies (4,15,16,17,18,19,20) and acceptable quality in the remaining five (6,20,21,22,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 shows the PRISMA flowchart illustrating the search strategy. Quality assessment for each article is demonstrated in Table I with high-quality in seven studies (4,15,16,17,18,19,20) and acceptable quality in the remaining five (6,20,21,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…The final review involved four cohort (4,16,18,19), six cross-sectional (15,20,21,22,23,24) and one each for mixed methods (6) as well as qualitative (17) studies. Four studies were conducted in the Netherlands (6,15,17,18), two studies in the United Kingdom/ England (19,24), and one study in Canada (20), Finland (16), Poland (21), Sri Lanka (22), United States of America (USA) (4) and Germany (23) respectively, with sample size ranging between 33 and 23777 respondents. Characteristics of reviewed articles are summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…The Activity Theory explains that elders who are active and healthy will be more content in their later lives. This theory indirectly affects the postretirement work concept (Perera and Weerakkody, 2019). While putting forward a differing view, Zacher and Rudolph (2017) have pointed out that they will be active before as well as after retirement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars found that FSA was the main determinant and it was highly impacted the social security of elders. As a result that Sri Lankan scholars identify EPF, ETF, Government pension have a positive impact on the social security of elders in Sri Lanka (Jayawardena & Arunathlake 2010;Perera 2011;Menike 2015;Perera & Weerakkody, 2019) Pension scheme for farmers established under Act, No 12 of 1987 was mainly targeted by the 2 million persons directly or indirectly engaged in the agriculture sector. Most farmers were working harder in youth through too late in life.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%